Decreasing pH affects Seagrass Epiphyte Communities. (April 2019) - Artika, S R; Kneer, D; Ambo-Rappe, R; Syahid, S; Teichberg, M
Abstract: Increasing CO2 in the atmosphere is affecting marine ecosystems, including seagrass beds. Epiphytes are a component of seagrass ecosystems. Epiphytes make a significant contribution as important primary producers in the food chain. Increasing atmospheric CO2 leads to a decrease in oceanic pH that can result in an unfavorable environment for the epiphytic community. This study was conducted to determine the effect of increasing CO2 on seagrass epiphytic communities and biomass. Using a field experiment, we manipulated dissolved carbon dioxide to 800 - 1000 ppm in line with the forecast increase in atmospheric CO2 levels in the year 2100. In situ C02 manipulations were conducted using an open-top mesocosm. The CO2 enrichment was conducted by adding CO2 at a concentration around 800 - 1000 ppm. This CO2 was injected directly using a pump and hose to the acrylic mesocosm chamber. Epiphyte community structure was affected, with an increase in the abundance of filamentous algae but a decrease in the coralline algae community in the CO2 enriched treatment units. Overall, CO2 enrichment had no effect on epiphyte biomass.